Factors Associated with Active Multiple Episode of Malaria in High High-Endemicity Area of Malaria (Jurnal kesehatan komunitas (Journal of community health), 2025)
Background: Timika is an endemic area for malaria in Indonesia. A receptive environment, behavioral factors, and knowledge of the local population cause the high prevalence of malaria in Timika. Objective: This study aims to determine the prevalence of recurrent episodes of malaria and factors that influence malaria episodes in highly endemic areas.Method: This study is an observational study with a cross-sectional design. This study was conducted in Naena Muktipur Village, Timika, Papua. Subjects were obtained using a purposive sampling method that met the inclusion and exclusion criteria. Demographic data, including age, address, ethnicity, education level, and occupation, were obtained through a questionnaire. Results: The subjects were predominantly women, had a high school education, and held non-risky jobs. As many as 72% of subjects had a history of malaria > 1 time, where malaria episodes were related to gender and behavior of staying overnight in the fields. Gender is related to the level of knowledge, while marital status is associated with the level of knowledge and behavior (p
Keywords: High endemicity, malaria episode, attitude